1994
DOI: 10.1103/physrevlett.73.2950
|View full text |Cite
|
Sign up to set email alerts
|

Can Galactic Observations Be Explained by a Relativistic Gravity Theory?

Abstract: We consider the possibility of an alternative gravity theory explaining the dynamics of galactic systems without dark matter. From very general assumptions about the structure of a relativistic gravity theory we derive a general expression for the metric to order (v/c) 2 . This allows us to compare the predictions of the theory with various experimental data: the Newtonian limit, light deflection and retardation, rotation of galaxies and gravitational lensing. Our general conclusion is that the possibility for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…By running the nucleosynthesis codes for different values of G, it was shown in Ref. [21] that a variation of ∆G/G = 0.2 on the values of the gravitational coupling was compatible with the observations of the primordial D, 3 He, 4 He and 7 Li abundances at 1σ level.…”
Section: Primordial Nucleosynthesissupporting
confidence: 62%
See 1 more Smart Citation
“…By running the nucleosynthesis codes for different values of G, it was shown in Ref. [21] that a variation of ∆G/G = 0.2 on the values of the gravitational coupling was compatible with the observations of the primordial D, 3 He, 4 He and 7 Li abundances at 1σ level.…”
Section: Primordial Nucleosynthesissupporting
confidence: 62%
“…Many of these attempts [2], although consistent with observations, were most often unsatisfactory from the theoretical point of view. Actually, it has been recently shown that under certain fairly general conditions it is unlikely that relativistic gravity theories can explain the flatness of the rotation curves of galaxies [3]. These conditions however do not exclude the class of generalizations of General Relativity that involve higher-derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The total gravitational acceleration felt by a planet embedded in the potential can be written as For α Y < 0(>0), gravity is enhanced (suppressed) on a large scale. The potential in can be derived in a relativistic gravity model that obeys the equivalence principle (Zhytnikov & Nester 1994). A Yukawa‐like contribution to the potential can be also connected to very specific mass terms which appear in addition to the field theoretical analogue of the usual Hilbert–Einstein Lagrangian (Babak & Grishchuk 2003).…”
Section: Basicsmentioning
confidence: 99%
“…For Δα > 0(<0), gravity is enhanced (suppressed) on large scales. The potential in can be derived in a relativistic gravity model that obeys the equivalence principle (Zhytnikov & Nester 1994). Although the Yukawa‐like form is quite specific, all long‐range deviations can be characterized empirically by an amplitude, Δα, and a length‐scale, λ.…”
Section: Linear Perturbation Equationmentioning
confidence: 99%